Procedural 3D Modeling Using Geometry Nodes in Blender : Discover the professional usage of geometry nodes and develop a creative approach to a node-based workflow - Lens, Siemen, ....- (Birmingham : Packt Publishing, 2023)
For anyone working in the computer graphics industry, understanding how to use Blender's new geometry nodes tools to manipulate and generate 3D geometry in a node-based workflow is an essential skill. In this book, you'll learn how to use the basic and intermediate features of geometry nodes that are a crucial part of your Blender roadmap. You'll start by understanding the different node inputs and outputs followed by the basic nodes you'll need throughout your geometry nodes projects. The book will show you how the node system works and enable you to put your newfound knowledge to use through exercises that involve modifying curves, meshes, and more. You'll work on a range of interesting projects such as creating a procedural plant, where you'll use nodes to generate the intricate details and variations of a plant in a procedural manner, and a spiderweb generator to refine your skills of cleaning up a node tree. Finally, you'll build a procedural LED panel using geometry nodes to generate the look of an LED panel. By the end of this book, you'll be able to overcome any geometry node issue confidently and make complicated geometry node trees exactly how you need them.
Keywords: Blender